Ex vivo expansion of hematopoietic progenitor cells is associated with downregulation of α4 integrin- and CXCR4-mediated engraftment in NOD/SCID β2-microglobulin-null mice - Jacques Foguenne; Ivano Di Stefano; Olivier Giet; Yves Beguin; André Gothot (Haematologica, 2009)
Background Several studies indicate that ex vivo cytokine-supported expansion induces defective hematopoietic stem cell engraftment. We investigated the role of α4 integrin, α5 integrin and CXCR4 in engraftment of unmanipulated and cytokine-treated human cord blood CD34+ cells.Design and Methods Uncultured or expanded CD34+ cells were infused in NOD/SCID-β2microglobulin-null mice. The function of α4, and α5 integrins and CXCR4 was assessed by incubating cells with specific neutralizing antibodies, prior to transplant. The activation state of α4 integrin was further tested by adhesion and migration assays.Results Neutralization of either α4 integrin or CXCR4 abolished engraftment of uncultured CD34+ cells at 6 week spost-transplant, while α5 integrin neutralization had no significant effect. However, after short-term ex vivo culture, blocking α4 integrin or CXCR4 did not affect repopulating activity whereas neutralization of α5 integrin inhibited engraftment. Using soluble vascular cell adhesion molecule-1 binding assays, we observed that α4 integrin affinity in fresh CD34+ cells was low and susceptible to stimulation while in cultured CD34+ cells, it was high and insensitive to further activation. In addition, stromal cell-derived factor-1 stimulated migration across vascular cell adhesion molecule-1 in fresh CD34+ cells but not in cultured CD34+ cells.Conclusions Our data show that ex vivo culture of hematopoietic progenitor cells is associated with downregulation of both α4 integrin- and CXCR4-mediated engraftment. Further investigations suggest that this is caused by supraphysiological increase of α4 integrin affinity, which impairs directional migration across vascular cell adhesion molecule-1 in response to stromal cell-derived factor-1. Such changes may underlie the engraftment defect of cytokine-stimulated CD34+ cells.